A Case of Surgical Treatment of Lower Molars in a Mesolithic Sample from a Cemetery on the Yuzhny Oleniy Ostrov, Karelia, Russia - A. V. Zubova; O. L. Pikhur; V. G. Moiseyev; A. A. Malyutina; A. V. Obodovskiy; O. A. Kalmina (Archaeology, Ethnology & Anthropology of Eurasia, 2024)
Here, we present the earliest case of surgical treatment of mandibular permanent molars known in Northern Eurasia. It concerns an aged woman buried at a Mesolithic cemetery on the Yuzhny Oleniy Ostrov (Island) in Lake Onega, southern Karelia, 8250–8050 cal BP. Our objective was to reconstruct the technology of surgical intervention, and to diagnose and describe the underlying condition. To do this, we carried out an examination of teeth and bone tissues of the upper and lower jaws and a traceological analysis of identified lesions. As we found, in the last few months of her life, the woman underwent several dental operations, including the extraction of the lower left third molar and, in a stepwise fashion, of fragments of the distal part of crown and lingual part of the distal root of the lower right first molar. The first operation was successful—the woman survived for at least two months after it had been performed. The second operation was also successfully performed at least two months before death, likely immediately after the trauma. The mesial part of the crown was removed just before death. No ancient cases where fragments of an injured tooth were removed are known to us. The removal of the lower third molar can be compared only with the earliest previously known case, described in a sample from the Pucará de Tilcara fortress in Northern Argentina (15th–16th centuries AD). Indications for surgery partly coincide in both cases, and include complications of apical periodontitis and the development of osteomyelitis. However, the technology of surgery and its logistics are different.